World outside my window - Bond, Ruskin (New Delhi Rupa Publications, 2016)
In this delightful little book, Ruskin Bond writes about some of the most interesting insects, birds, trees and flowers he has observed. As a person with a deep and abiding connection with all things natural, he brings keen observation and delightful details into his pieces. From the butterfly, dragonfly, scorpion and ant lion to different varieties of cacti, semul trees, the jasmine flower and the wild flowers found in the Himalayan region, as well as birds of the hills and urban areas like Delhi, Bond describes them all. This book is a handy guide for anyone who is interested in exploring the natural world as well as all those who love reading about nature.
Keywords: Non-fiction